2023
DOI: 10.3390/su15118472
|View full text |Cite
|
Sign up to set email alerts
|

Cold Ironing Implementation Overview in European Ports—Case Study—Croatian Ports

Roko Glavinović,
Maja Krčum,
Luka Vukić
et al.

Abstract: Cold ironing technology, recognized as a tool to reduce emissions while ships are at berth, has been introduced in several European ports aligning with the international and European environmental and legal framework for reducing greenhouse gas emissions. The study aims to identify the prospects for cold ironing technology’s introduction into Croatian state-owned ports according to European sustainable conditions. The authors surveyed a group of port experts and stakeholders. Response analysis showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The study emphasizes the importance of coordinated policies and investments among countries to maximize the technology's environmental and economic advantages. A study by Glavinovic et al [28] revealed that 40% of these ports currently have high-voltage connections over 1 kV, crucial for effective cold ironing implementation. However, a significant portion, 60%, lacks adequate infrastructure, indicating a need for substantial investment.…”
Section: Discussionmentioning
confidence: 99%
“…The study emphasizes the importance of coordinated policies and investments among countries to maximize the technology's environmental and economic advantages. A study by Glavinovic et al [28] revealed that 40% of these ports currently have high-voltage connections over 1 kV, crucial for effective cold ironing implementation. However, a significant portion, 60%, lacks adequate infrastructure, indicating a need for substantial investment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, C. Trozzi and R. Vaccaro (2021) categorized them into four aspects: air pollution, water pollution, waste generation, and noise production [7] . On the other hand, Ruiz-Guerra (2019) grouped them into four major categories: impacts on climate change, impacts on air quality, impacts on water quality, and impacts on the health of surrounding community members [8] . These classifications demonstrate the multifaceted negative impacts of ports on the environment, including deterioration of air and water quality, waste generation and disposal issues, and harm to the health of nearby community residents.…”
Section: Adverse Environmental Impacts Of Portsmentioning
confidence: 99%